The Flipped Classroom Optimized Through Gamification and Team-Based Learning - Lopes Sergio Francisco Sargo Ferreira; Simões Jorge Manuel de Azevedo Pereira; Lourenço Justino Marco Ronda; Morais José Carlos Pereira de (De Gruyter, 2024)
The increase in digital teaching and learning methodologies creates the opportunity for new educational approaches, both in terms of pedagogical practice and in the availability of new technological tools. The flipped classroom as an active teaching methodology is one example of blended learning (b-learning), which aims to harmonize and enhance the fusion of face-to-face teaching with online teaching, allowing students to get better use of both face-to-face contact with classmates and professors and digital teaching resources. However, active teaching methodologies allow us to merge educational techniques from different methodological approaches, for example, gamification and team-based learning (TBL), among others. This study aims to demonstrate how to implement a flipped classroom with the possibility of integrating gamification and TBL, indicating possibilities and challenges to overcome, through the comparative study and research carried out with students in higher education. The study was conducted with a group of 88 students from the engineering and technology fields, which showed that students have a very positive perception of active teaching methodologies and their teaching and learning techniques, especially those involving digital. Data collection was performed by a survey submitted to quantitative analysis using the Software SPSS version 28.